2018
DOI: 10.1111/jre.12598
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide association study identifies an association between variants in EFCAB4B gene and periodontal disease in an Italian isolated population

Abstract: Background and Objective Periodontitis in one of the most prevalent dental diseases. Despite numerous studies have investigated its aetiopathogenetic factors, few works have focused on its genetic predisposition and most of them took into account only candidate genes. Therefore, we conducted a Genome Wide Association Study in an Italian isolated population aimed at uncovering genetic variants that predispose to this disorder. Methods Diagnosis of chronic periodontitis was made following the criteria of the Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
(57 reference statements)
1
21
0
Order By: Relevance
“…Other studies have implicated numerous loci without reaching genome‐wide statistical significance levels and/or demonstrating replication in an independent cohort. For example, a recent study among a small Italian population reported associations between EFCAB4B polymorphisms (rs242016 showing the strongest evidence of association) and localized periodontitis …”
Section: Genomics Of Traditional Clinical Definitions Of Oral and Denmentioning
confidence: 97%
See 2 more Smart Citations
“…Other studies have implicated numerous loci without reaching genome‐wide statistical significance levels and/or demonstrating replication in an independent cohort. For example, a recent study among a small Italian population reported associations between EFCAB4B polymorphisms (rs242016 showing the strongest evidence of association) and localized periodontitis …”
Section: Genomics Of Traditional Clinical Definitions Of Oral and Denmentioning
confidence: 97%
“…For example, a recent study among a small Italian population reported associations between EFCAB4B polymorphisms (rs242016 showing the strongest evidence of association) and localized periodontitis. 24 Interestingly, several loci have been highlighted as showing suggestive evidence of association (with P values typically ranging between 5 × 10 −6 and 5 × 10 −8 ) in more than one (independent) genome-wide association study and thus warrant attention. A prime example is SIGLEC5 (rs12461706), which was reported in a recent study of aggressive periodontitis 30 and was the only locus that met genome-wide statistical significance criteria in a large, consortium meta-analysis of chronic periodontitis that combined clinical and self-reported data.…”
Section: Periodontal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Sanders et al (2017) found an association with TSNAXDISC1 noncoding mRNA (lead signal: rs149133391) in a large population of Hispanics and Latinos and the variant was replicated independently in an African-American but not in a European-American sample. In a genetically isolated population in Italy, four SNPs in the EFCAB4B gene (rs242016, rs242014, rs10491972, and rs242002) were found to be signi cantly associated with localized periodontitis but the ndings have not been replicated so far [18].…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have investigated genomewide associations of different periodontitis phenotypes [2,8]. In terms of the GWA approach in chronic periodontitis, several studies using various case de nitions and populations of different ethnic origins have been published [9][10][11][12][13][14][15][16][17][18][19][20][21]. Only a few of these studies reported associations on the level of stringent genome-wide signi cance level (p-value < 5 × 10 − 8 ) [16,18,21,22].…”
Section: Introductionmentioning
confidence: 99%